2022
DOI: 10.3390/economies10040084
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Governance and Gender Diversity Matter in Firm Performance (ROE)? Empirical Evidence from Jordan

Abstract: The aim of this paper was to examine the effect of managerial/board gender diversity and corporate governance structure on firm performance in a Jordanian business environment—a developing economy that has a distinct environment from that of developed economies. The current study focuses on the unique context of an emerging economy (i.e., Jordan). Data were collected from nonfinancial companies listed on the Amman Stock Exchange from 2018 to 2020. Data analysis was carried out using the random-effects estimato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 119 publications
2
16
0
2
Order By: Relevance
“…Studies that report of a positive association between gender diversity and firm performance explain it in terms of women having greater analytical skills and their ability to coordinate activities with much greater ease than men while upholding company values and strategy (Heskett, 2015;Ali et al, 2021;Meah et al, 2021;Simeonescu et al, 2021;Nyeadi et al, 2021;Awan and Raza, 2022). Those that report of negative or insignificant relationship between gender diversity and firm performance mostly adduce it to the "reduced powers of female directors on corporate boards", for example, by not making them serve on any advisory or monitoring committees (Zalata et al, 2019b), which often culminates in a weaker monitoring and advisory role (Alshirah et al, 2022;Post and Byron, 2014;Vuong, 2021;Simeonescu, 2021). Besides, studies thta report of nonlinear or threshold effects (Gharbi and Othmani, 2022) often support the critical mass theory, which posits that a sufficient number of women on boards are required so that they can have real influence on board decisions and consequently affect corporate outcomes favourably (Torchia et al, 2011;Gharbi and Othmani, 2022).…”
Section: Board Gender Diversity and Firm Performancementioning
confidence: 99%
“…Studies that report of a positive association between gender diversity and firm performance explain it in terms of women having greater analytical skills and their ability to coordinate activities with much greater ease than men while upholding company values and strategy (Heskett, 2015;Ali et al, 2021;Meah et al, 2021;Simeonescu et al, 2021;Nyeadi et al, 2021;Awan and Raza, 2022). Those that report of negative or insignificant relationship between gender diversity and firm performance mostly adduce it to the "reduced powers of female directors on corporate boards", for example, by not making them serve on any advisory or monitoring committees (Zalata et al, 2019b), which often culminates in a weaker monitoring and advisory role (Alshirah et al, 2022;Post and Byron, 2014;Vuong, 2021;Simeonescu, 2021). Besides, studies thta report of nonlinear or threshold effects (Gharbi and Othmani, 2022) often support the critical mass theory, which posits that a sufficient number of women on boards are required so that they can have real influence on board decisions and consequently affect corporate outcomes favourably (Torchia et al, 2011;Gharbi and Othmani, 2022).…”
Section: Board Gender Diversity and Firm Performancementioning
confidence: 99%
“…Consequently, Ntim (2015) demonstrated that greater commitment to increasing the number of women serving on boards is rewarded with higher market valuation, as proved by Tobin's Q. However, Kagzi and Guha (2018) and Alshirah et al (2022) found that female board members have no special relationship with profitability. Alshirah et al (2022) suggested that skill and qualification should weigh more heavily than diversity when appointing women to boards.…”
Section: Female Supervisory Board Membersmentioning
confidence: 98%
“…However, Kagzi and Guha (2018) and Alshirah et al. (2022) found that female board members have no special relationship with profitability. Alshirah et al.…”
Section: Empirical Literature and Hypotheses Developmentmentioning
confidence: 99%
“…ROE was also considered to be one of the measures to determine the effectiveness of the management of a firm using its firm's assets to make a profit. Several studies have used ROE to measure the firms' performance (Alodat et al, 2021;Alshirah et al, 2022;Bawazir et al, 2021). Some of the previous research found mixed results when analyzing the CG mechanisms with firm performance.…”
Section: Return On Equity (Roe)mentioning
confidence: 99%
“…Some of the previous research found mixed results when analyzing the CG mechanisms with firm performance. Alshirah et al (2022) concluded that ROE had a positive insignificant relationship with women directors; a negative significant relationship with board size.…”
Section: Return On Equity (Roe)mentioning
confidence: 99%